The Effectiveness of Principal Leadership in Improving Teacher Performance - Harliansyah, Harliansyah (Educationist: Journal of Educational and Cultural Studies, 2022)
This study aims to describe the empirical picture and analyze how much influence the effectiveness of the principal's leadership has in improving teacher performance from the variables of leading behavior, the efforts made by the principal, as well as the supporting and inhibiting factors of the effectiveness of the principal's leadership in improving teacher performance in the City of Samarinda and the type of research, is qualitative research with the kind of case study. The data sources for this study were the principal, vice principal, teachers, and administrative staff at SMK Samarinda City-procedures for collecting and recording data using interviews, observation, and documentation studies. The data analysis techniques used are data reduction, data presentation, and conclusions. They are checking or checking the validity of the data using a credibility test. The research results obtained are: (1) To improve teacher performance, The principal manages the placement of teaching and educational staff in this school by the certificates owned, and the development of teaching staff in schools is by providing opportunities for teachers to solve learning and non-learning problems professionally through action research in a controlled manner until finally, teacher performance improves, besides that both teaching and educational staff are included in the training to improve performance. (2) Efforts made by the principal to improve teacher performance include supervision and guidance from the principal or deputy principal in the teacher learning process, (3) supporting factors in improving teacher performance are providing facilities to support teacher performance such as laptops and learning devices. In contrast, the inhibiting factors are natural conditions and the ever-changing curriculum.